2021
DOI: 10.21203/rs.3.rs-228617/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using an online CBT-based intervention to improve academic performance in students with low mood: A pre-post study with historical control

Abstract: Background Online CBT-based interventions have shown potential to improve mental health in university students. However, their impacts in West Asian cultures and on educational achievement have yet to be fully investigated. This study aims to explore the feasibility, acceptability and potential effectiveness of a self-directed, internet-delivered, cognitive-behavioural skills training program (MoodGYM) in reducing depression and improving academic performance in university students in the United Arab Emirates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…There is been little research on the impact of digital mental health interventions on students' academic functioning [12]. However, a study conducted in United Arab Emirate (UAE) reported improved academic performance following the use of moodgym [30].…”
Section: Discussionmentioning
confidence: 99%
“…There is been little research on the impact of digital mental health interventions on students' academic functioning [12]. However, a study conducted in United Arab Emirate (UAE) reported improved academic performance following the use of moodgym [30].…”
Section: Discussionmentioning
confidence: 99%